PREVALENCE OF HEPATITIS '˜B' AND '˜C' IN ORTHOPAEDICS PATIENTS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Khan, Muhammad Shoaib; Jamil, Muhammad; Jan, Sakhi; Zardad, Shoaib; Sultan, Shahid; Sahibzada, Ahmed Sohail (Journal of Ayub Medical College Abbottabad, 2007)
Background: Hepatitis B and C is a common global health problem and is spreading rapidly in developing countries due to lack of health education, poverty and illiteracy. Both of these infections can be transmitted through blood or body fluids, tattooing, through infected instruments, unsafe shave by barbers and sexual contact. Medical personnel are most exposed to these infections. There should be proper preventive measures to prevent its spread in the community. Methods: This is a descriptive study carried out from July 2003 to July 2004 on 1630 patients admitted in the department of Orthopaedics Ayub Teaching Hospital Abbottabad. Patients of either sex, of all ages undergoing surgery were included in the study. All patients underwent screening for Hepatitis-B and Hepatitis-C and confirmed by Elisa method in positive patients. Results: Out of 1630 patients 1205 (73.92%) were male and 425 (26.07%) were female. Hepatitis B and C was present in 84 (5.15%) patients. Out of 84 infected patients 51 (3.12%) were suffering from hepatitis C and 33 (2.02%) were suffering from hepatitis B. In 2 (0.12%) patients both hepatitis B and C infections were present. Out of 51 hepatitis C patients, 33 (64.71%) were male and 18 (35.29%) were female. Out of 33 hepatitis B patients, 28 (84.85%) were male and 5 (15.15%) were female patients. Among the predisposing factors previous history of surgery was positive in 18 (21.43%) patients, history of blood transfusion in 13 (15.47%) patients, dental procedure was in 7 (8.33%) patients, and abroad visit in 4 (4.76%) patients. Conclusion: The prevalence of hepatitis B and C in orthopaedic patients is quite high with the common risk factors: previous history of surgery or blood transfusion. Therefore, all patients which need surgery should be routinely screened for hepatitis B & C to prevent transmission to other patients, medical staff. There should be separate operation theatres facilities for these patients. There should be policy by the Government for protection of medical personnel who are exposed to these patients and there should be compensation for those who get infected with these infections during their service otherwise the medical personnel especially surgeons will hesitate doing surgeries on hepatitis B and C infected patients. Key Words: Prevalence, Hepatitis B, Hepatitis C, Orthopaedic patients